Gender differences in the association between oral health literacy and oral health-related quality of life in older adults - Lee, Chia-Jung; Ho, Mu-Hsing; Joo, Jee Young; Montayre, Jed; Lin, Yen-Kuang; Chang, Chia-Chi; Liu, Megan F. (BMC oral health, 2022)
Poor oral health affects quality of life; oral health literacy studies are increasing as it plays an essential role in promoting oral health. However, little is known regarding the gender differences in oral health literacy and oral health-related quality of life (OHRQoL) among older adults. This study aimed to explore the gender differences in oral health literacy and OHRQoL among community-dwelling older adults in Taiwan. A cross-sectional study design with convenience sampling was undertaken to recruit participants at two community service centres. Data were collected using a structured survey consisted of the demographic characteristics, instrumental activities of daily living, nutrition assessment, oral health literacy and OHRQoL. The logistic regression was used to examine the gender differences in the relationship between oral health literacy and OHRQoL. A total of 202 participants completed the survey. Of which 56.4% (n = 114) were female. Logistic regression analyses showed that after controlling for age, instrumental activities of daily living, nutrition, education level, and average monthly income, better oral health literacy was associated with better oral health quality of life (p = 0.006) in men. The relationship between oral health literacy and OHRQoL was only significant for men. No significant relationship between women's oral health literacy and their OHRQoL. However, good OHRQoL is an integral part of overall health, but it is affected by differences in oral health and the accessibility of healthcare services. We suggest that gender-specific oral health literacy education should be offered through community health-education programs.